Fast contraband detection in large capacity disk drives. (March 2015) - Penrose, Philip; Buchanan, William J.; Macfarlane, Richard
Abstract: In recent years the capacity of digital storage devices has been increasing at a rate that has left digital forensic services struggling to cope. There is an acknowledgement that current forensic tools have failed to keep up. The workload is such that a form of 'administrative triage' takes place in many labs where perceived low priority jobs are delayed or dropped without reference to the data itself. In this paper we investigate the feasibility of first responders performing a fast initial scan of a device by sampling on the device itself. A Bloom filter is used to store the block hashes of large collections of contraband data. We show that by sampling disk clusters, we can achieve 99.9% accuracy scanning for contraband data in minutes. Even under the constraints imposed by low specification legacy equipment, it is possible to scan a device for contraband with a known and controllable margin of error in a reasonable time. We conclude that in this type of case it is feasible to boot the device into a forensically sound environment and do a pre-imaging scan to prioritise the device for further detailed investigation.